Performance enhancement of a trapped-vortex combustor for gas turbine engines using a novel hybrid-atomizer. (15th April 2018) - Li, Mingyu; He, Xiaomin; Zhao, Yuling; Jin, Yi; Yao, Kanghong; Ge, Zhenghao
Highlights: A workable TVC fueled by two different atomizers is designed and investigated. A novel hybrid-atomizer is designed and adopted for cavity fueling. Comparison experiments are conducted on the TVC fed by two different atomizers. More excellent performance is achieved by the TVC fueled by novel hybrid atomizer. Abstract: A novel hybrid-atomizer, combining the spray characteristics of pressure-swirl, airblast and fan atomizers, was designed and adopted for cavity fueling in a trapped vortex combustor (TVC). Furthermore, comparison experiments were conducted under atmospheric pressure to investigate the combustion characteristics of the combustor fueled using the novel hybrid atomizer and a simplex pressure-swirl atomizer. The discrepancies were directly explored in terms of ignition, lean blowout (LBO) limit, and combustion efficiency. The results indicate that the novel hybrid atomizer achieves significant advantages in terms of the combustion characteristics when compared to the simplex pressure-swirl atomizer. The outer-cavity ignition FAR achieved by the novel hybrid atomizer is 50% lower than pressure-swirl atomizer at Mach 0.25 and 0.29, with an inlet temperature of 373 K. In addition, the LBO limits acquired by the novel hybrid atomizer are lower than those of the pressure-swirl atomizer within the full range of operating conditions. Furthermore, a higher combustion efficiency is achieved by the novel hybrid atomizer compared to the pressure-swirl atomizer under most operating regimes.